Pastoral Therapy: Problematizing the Imbokodo Image through the Bosadi Theorization - Phalatsi-Shilubana, Mmamajoro (Journal of Cultural Analysis and Social Change, 2026)
“I am a rock” followed by the isiZulu expression “Wathinta abafazi, wathinta imbokodo” (“you strike a woman, you strike a rock”) has historically functioned as a cultural metaphor affirming women’s strength and resilience in African societies. However, within contemporary African contexts characterised by pervasive Gender-Based Violence (GBV), this imbokodo imagery warrants critical interrogation. While celebratory, the metaphor risks reinforcing gendered expectations that normalise women’s suffering, silence vulnerability, and valorise endurance in ways that sustain patriarchal harm. Drawing on Bosadi theorisation and pastoral therapeutic discourse, this paper problematises the imbokodo image as a cultural and theological narrative that may inadvertently contribute to the persistence of GBV against women and girls. Through a critical literature-based approach, the study demonstrates how Bosadi theorisation offers an African feminist epistemological framework that disrupts essentialised constructions of womanhood and reclaims women’s embodied agency, dignity, and right to care. The paper argues that pastoral therapy informed by Bosadi theorisation can generate liberative counter-narratives that centre women’s lived experiences, affirm vulnerability as human rather than pathological, and promote self-care as an ethical and spiritual imperative. In doing so, the study contributes to African-centred scholarly conversations on gender, culture, and religion by advancing a decolonial pastoral praxis responsive to GBV in African contexts.